De Flower / Clarice Elsa Alan - Alan, Clarice Elsa (2021)
The business conducted is a service of selling handicrafts. The business is wholly owned by students and the products sold are the result of their own handicrafts, not purchased from any other party. This is because the owner of this business has a hobby of knitting yarn. In a day, more than 3 to 5 flower buds can be produced. The handicrafts sold are yarns that are knitted into flowers. This marketing is carried out online by using the "Facebook page" platform. The initial cost for this business is in the RM50 range. This is because this business is a small business only. Labour is not used except by the owner himself. The return that can be obtained from this business is between RM150 to RM200.